Triceps surae muscle hypertrophy is greater after standing versus seated calf-raise training - Kinoshita, Momoka; Maeo, Sumiaki; Kobayashi, Yuuto; Eihara, Yuuri; Ono, Munetaka; Sato, Mauto; Sugiyama, Takashi; Kanehisa, Hiroaki; Isaka, Tadao (Frontiers in Physiology, 2023)
The triceps surae muscle plays important roles in fundamental human movements. However, this muscle is relatively unresponsive to resistance training (difficult to hypertrophy) but prone to atrophy with inactivity compared with other muscles. Thus, identifying an effective training modality for the triceps surae is warranted. This study compared triceps surae muscle hypertrophy after standing/knee-extended versus seated/knee-flexed plantarflexion (calf-raise) training, where the gastrocnemius is lengthened and shortened, respectively. Methods: Fourteen untrained adults conducted calf-raise training with one leg in a standing/knee-extended position and the other leg in a seated/knee 90°-flexed position at 70% of one-repetition maximum. Each leg performed 10 repetitions/set, 5 sets/session, 2 sessions/week for 12 weeks. Before and after the intervention, MRI scans were obtained to assess muscle volume of each and the whole triceps surae. Results: Muscle volume significantly increased in all three muscles and the whole triceps surae for both legs (P≤0.031), except for the gastrocnemius muscles of the seated condition leg (P=0.147-0.508). The changes in muscle volume were significantly greater for the standing than seated condition leg in the lateral gastrocnemius (12.4% vs 1.7%), medial gastrocnemius (9.2% vs 0.6%), and whole triceps surae (5.6% vs 2.1%) (P≤0.011), but similar between legs in the soleus (2.1% vs 2.9%, P=0.410). Conclusions: Standing calf-raise was by far more effective, therefore recommended, than seated calf-raise for inducing muscle hypertrophy of the gastrocnemius and consequently the whole triceps surae. This result and similar between-condition hypertrophy in the soleus collectively suggest that training at long muscle lengths promotes muscle hypertrophy.